Sistem Static Inverter Pada Kereta Rel Listrik HOLEC-BN - Taufik Hidayat (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2010)
Static inverter (SIV) system in electric railcar Holec-BN with VVVF (variable voltage variable frequency) technology, change a nominal input voltage 1.500 VDC into output voltage 380 VAC, three phase, 50 Hz, and 110 VDC and 137 VDC. SIV serve voltage as a compressor system, ventilation, light lamps, drive/brake control, etc. Loads that SIV serve it can be stopped to operate in an emergency conditions. This helps a system or loads or system to maintain a working if one of SIV stopped and it is still operated if both SIV have fail. As mentioned above, Holec-BN electric railcar operate two units SIV on each trainset of electric railcar. A frequency of failure and damage of SIV in Holec-BN electric railcar classified a high. In order to reliability of this electric railcar can be maintained on reasonable level, there is need a improvement steps to prevent the failure and damage to continue. Higher reliability is need in order to avoidable the electric railcar also in high so that it have ability to meet a hope for public who use the service in order to obtain railway transportation with safe, secure, confortable, reliable, punctual, and so on.